The concept of teachers and students from the perspective of the Quran - Putra Mahendra Gunawan Nasution (Institute of Computer Science (IOCS), 2026)
Contemporary Islamic education faces serious challenges in the form of reducing the role of teachers to mere technical instructors and the tendency to position students as merely cognitively oriented learning objects. This condition has the potential to erode the moral and spiritual dimensions of Islamic education, which are truly rooted in the values ??of the Quran. Therefore, this study aims to analyze in-depth the concept of teachers and students from the perspective of the Quran and its implications for contemporary Islamic education practices. This study uses a qualitative approach with a library research type. The primary data sources are Quranic verses relevant to the theme of education, and articles from accredited national scientific journals serve as secondary sources. The data were analyzed using content analysis techniques with a thematic-interpretive approach to explore the pedagogical meaning, educational relationships, and prophetic values ??contained in the Quranic text. The results of the study indicate that the Quran positions teachers as murabbi, moral role models, and agents of social transformation that integrate scientific, moral, and spiritual dimensions, while students are understood as active subjects who have natural dispositions, intellectual potential, and moral responsibility. This study concludes that the concept of teachers and students from the perspective of the Quran has strategic relevance for the development of contemporary Islamic education that is holistic, character-based, and oriented towards the formation of faithful, noble, and socially responsible individuals without losing the foundation of Quranic values.